Safety First, Then Condoms: Commercial Sex, Risky Behavior, and the Spread of HIV/AIDS in Managua, Nicaragua - Willman, Alys (2012)
This study analyzes the commercial sex market in Managua, Nicaragua, to understand risky behavior among sex workers. While health risks are a major concern for sex workers, the risk of violence weighs more heavily in decision making, such that they more often take risks to their health than to their immediate, physical well-being. These concerns are reflected in the lower premiums sex workers charge for unprotected sex (39 percent more for vaginal sex without a condom) compared with risks of violence, such as accompanying a client to an unknown place (a 118 percent premium). Risk behaviors reflect a rational calculation of actual risk: while only 9 percent of the sample knew anyone diagnosed with HIV, nearly 44 percent of sex workers had been assaulted. These observations indicate the need to consider sex workers' physical safety in policies to contain the spread of HIV/AIDS and other sexually transmitted diseases.